2015
DOI: 10.1002/jmv.24234
|View full text |Cite
|
Sign up to set email alerts
|

BK and JC polyomavirus infections in Tunisian renal transplant recipients

Abstract: The aim of this prospective study was to investigate the rate of BK (BKPyV) and JC (JCPyV) polyomavirus infections and their influence on allograft function in Tunisian renal transplant recipients. A total of 72 renal transplant recipients were studied. BKPyV and JCPyV were detected and quantified by real-time PCR in urine and plasma. Demographic and laboratory characteristics were collected for each patient. Polyomavirus DNAuria was detected in 54 (75%) of renal transplant recipients: 26 (36%) had BKPyV DNAur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 47 publications
2
10
0
Order By: Relevance
“…Predominantly, JCPyVAN is described as a decline of renal function in conjunction with detection of JCPyV in the urine specimen and should be confirmed with compatible histologic finding, positive SV40 staining. The majority of nephropathy cases did not have JCPyV viremia but only JCPyV viruria, which is consistent with our patient . A report from Querido et al .…”
Section: Discussionsupporting
confidence: 92%
“…Predominantly, JCPyVAN is described as a decline of renal function in conjunction with detection of JCPyV in the urine specimen and should be confirmed with compatible histologic finding, positive SV40 staining. The majority of nephropathy cases did not have JCPyV viremia but only JCPyV viruria, which is consistent with our patient . A report from Querido et al .…”
Section: Discussionsupporting
confidence: 92%
“…In this study, JCV was detected in 27.6% of all test patients. Other studies of transplant patients and normal population have observed a JCV prevalence between 9.5-38% [12,13,14]. Indeed, Boukoum et al [13] detected JCV viruria in 13% of all healthy individuals, but in 38% of all kidney transplant recipients in their test population.…”
Section: Discussionmentioning
confidence: 90%
“…There was no significant differences observed between control and study groups. Boukoum et al [12] in their analysis of occurrence polyomaviruses, noted that JCV was detected in 9.5% of all urine samples, whereas JCV was not detected in plasma.…”
Section: Discussionmentioning
confidence: 99%
“…All the previous BKPyV and JCPyV results from healthy individuals were compared with results from KTx previously described [7]. Any polyomavirus urinary shedding was significantly more frequent in KTx than in healthy persons and the urinary viral loads of the two viruses were also significantly higher in KTx than healthy group.…”
Section: Discussionmentioning
confidence: 99%
“…Plasma and urine samples were also collected from 72 kidney transplant recipients (KTx) enrolled in a prospective study described elsewhere [7]. Ethical permission on this research study was granted by the Ethics and Research Committee of the Fatouma Bourguiba hospital.…”
Section: Study Participants and Sample Collectionmentioning
confidence: 99%